Checklist with notes on rubiaceae of Fraser’s Hill, Pahang and Selangor - Zohari, Ahmad Fitri; Nik Hashim, Nik Hazlan; Nik Ali, Nik Norafida; Mohd Said, Mohd Nizam; Mustafa Bakray, Nur ‘Aqilah; Zulkifli, Mohammad Khairul Faizi; Zainuddin, Ahmad Firdaus; Wan Ismail, Wan Norilani; Engku Ariff, Engku Azlin Rahayu; Kusin, Mazlin; Mohamad, Norazlinda; Abd Rasid, Khairunnisaa; et al. (Universiti Teknologi MARA (UiTM), 2024)
This paper reports the checklist and notes of Rubiaceae in the lower montane forest of Fraser’s Hill in Pahang and Selangor. A total of 48 species from 23 genera were recorded, with Lasianthus being the most diverse genus with seven species. Thirteen species, viz. Argostemma yappii, Ixora micrantha, Lasianthus filiformis var. bracteatus, L. politus, L. pterospermus, L. robinsonii, Pavetta salicina, P. wallichiana, Psydrax sp. 3., Psydrax sp. 6, Tarenna sp. 6, Timonius diffusus and T. oreophilus are endemic to Peninsular Malaysia. The research indicated that Rubiaceae exhibits diversity in the lower montane forest of Fraser’s Hill, so suggesting the necessity for protection and conservation of the area. Additional research is necessary to further comprehension of this family's diversity